Elevated levels of human endogenous retrovirus-W transcripts in blood cells from patients with first episode schizophrenia. - Yao, Y; Schröder, J; Nellåker, C; Bottmer, C; Bachmann, S; Yolken, R; Karlsson, H (2008)
We previously reported on the differential presence of transcripts related to the human endogenous retrovirus (HERV)-W family in cerebrospinal fluid and plasma from patients with first-episode schizophrenia compared with control individuals. Whether this is a consequence of qualitative or quantitative differences in transcription of genomic regions harboring HERV-W elements is not known. The purpose of the present study was therefore to characterize the transcribed HERV-W elements in mononuclear cells obtained from 30 patients first hospitalized for schizophrenia-related psychosis and from 26 healthy control individuals. We observed elevated total levels of HERV-W gag (2.1-fold, P < 0.01) but not env transcripts in the cells of patients compared with controls. By using the melting temperatures of the amplicons as a proxy marker for sequence identity, no absolute qualitative differences was detected between the two groups. Mapping of the detected transcripts identified several intronic and intergenic HERV-W elements transcribed in the cells, including elements previously considered transcriptionally silent. Element-specific assays revealed elevated levels of intronic transcripts containing HERV-W gag sequence from the putative gene PTD015 on chromosome 11q13.5 (1.6-fold, P < 0.05) in the patients compared with the controls. Thus, studies aiming to further understanding of complex human disease such as schizophrenia may need to be extended beyond the strictly protein-coding fraction of the transcriptome.